Food Insecurity in ECOWAS Region: The Nexus of Climate Change and Macroeconomic Dynamics - Aroyehun, Adeyinka Richard; Henri-Ukoha, Adanna (Journal of Multidisciplinary Research Advancements, 2025)
Food insecurity remains a recurrent issue in the Economic Community of West African States (ECOWAS), worsened by the combined constraints of climatic unpredictability and macroeconomic volatility. This study examines the interaction between climate change factors—such as precipitation, temperature, and CO₂ emissions—and macroeconomic elements, including food production, exports, imports, inflation, GDP, population, and consumer prices, to assess their impact on food security in ECOWAS member countries from 2000 to 2023. By employing panel econometric models, including Common Effects, Fixed Effects, and Random Effects, along with thorough diagnostic tests, the research reveals that food production, temperature, and exports significantly enhance food security. However, irregular rainfall and reliance on imports tend to have a detrimental effect. Interestingly, the Consumer Price Index and population growth show varied impacts, highlighting the structural and institutional differences among the member states. The findings underscore the urgent need for integrated regional policies that tackle climate change resilience, stable macroeconomic conditions, and agricultural productivity simultaneously. Strategic actions aimed at curbing inflation, encouraging climate-smart farming, facilitating trade, and improving infrastructure are essential for fostering sustainable food systems across ECOWAS. To effectively combat food insecurity in the region, comprehensive policy frameworks that focus on climate adaptation, economic stabilization, and equitable agricultural development are crucial. Additionally, regional cooperation can play a vital role in addressing food security challenges amid climate change and shifting global economic trends.